PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS X SMK N 3 SIJUNJUNG - AFDEL FAJRI KEMRI, Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2019)
This research aims to determine the effect of creative problem solving (CPS) and activies on learning outcomes in the class X of SMK Negeri 3 Sijunjung. The type of research used was quasi eksperimental design with the hottest control group design. The research instrument used was a learning achievement test and a student learning activity questionnaire. The results of the reserch stated that 1) There is a significant influence on the application of creative problem solving learning models in improving the learning outcames of fine art in the class X SMk Negeri 3 Sijunjung, 2) There is an effect of applying the creative problem solving model in improving student learning outcomes with high learning activities on fine arts material, 3) There is an effect of applying the creative problem solving model in improving student learning outcomes with low learning activities on fine arts material.